Rifabutin: a repurposed antibiotic with high potential against planktonic and biofilm staphylococcal clinical isolates - Ferreira, Magda; Pinto, Margarida; Aires-da-Silva, Frederico; Bettencourt, Ana; Gaspar, Maria Manuela; Aguiar, Sandra Isabel (Frontiers in Microbiology, 2024)
Staphylococcus aureus poses a significant threat as an opportunistic pathogen in humans, and animal medicine, particularly in the context of hospital-acquired infections (HAIs). Effective treatment is a significant challenge, contributing substantially to the global health burden. While antibiotic therapy remains the primary approach for staphylococcal infections, its efficacy is often compromised by the emergence of resistant strains and biofilm formation. The anticipated solution is the discovery and development of new antibacterial agents. However, this is a time consuming and expensive process with limited success rates. One potential alternative for addressing this challenge is the repurposing of existing antibiotics. This study investigated the potential of rifabutin (RFB) as a repurposed antibiotic for treating S. aureus infections. The in vitro antimicrobial activity of rifabutin was determined, in parallel to vancomycin, in 114 clinical isolates recovered from invasive staphylococcal disease. The study demonstrated that RFB MIC ranged from 0.002 to 6.250 µg/mL with a MIC50 of 0.013 µg/mL. RFB also demonstrated high anti-biofilm activity in a subset of 40 clinical isolates, with confirmed biofilm formation, with no significant MBIC50 differences observed between the MSSA and MRSA strains, in contrast to that observed for the VAN. These results highlight the promising efficacy of RFB against staphylococcal clinical isolates with different resistance patterns, whether in planktonic and biofilm forms.